1995
DOI: 10.1515/hfsg.1995.49.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophenolics from High Molecular Weight Chlorinated Organics Isolated from Bleached Kraft Mill Effluents

Abstract: Extended abiotic incubation and alkaline hydrolysis of chlorinated high molecular weight (HMW) organics (>400D) isolated from bleached kraft mill effluents (BKME) were used to release bound Chlorophenolics. Incubation experiments showed a temperature dependent slow release of 4,5-dichloroguaiacol (4,5-DCG), 3,4,5-trichloroguaiacol (3,4,5-TCG), 4,5,6-trichloroguaiacol (4,5,6-TCC), tetrachloroguaiacol (TeCG), 6-chlorovanillin (6-CVa) and 5,6-dichlorovanillin (5,6-DCVa) from HMW material. Alkaline hydrolysis of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…60 ± 62 One of promising approaches to oxidative destruction of residual lignin in industrial pulps during bleaching is the biotechnological method. 63,64 Molecular chlorine is widely employed in the pulp industry for oxidation of lignin during the pulp bleaching, however, its application is accompanied by concomitant formation of a number of toxic aromatic chlorine-containing products, 65,66 including dioxins. 67 The use of sodium hypochlorite for the pulp bleaching is accompanied by the formation of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…60 ± 62 One of promising approaches to oxidative destruction of residual lignin in industrial pulps during bleaching is the biotechnological method. 63,64 Molecular chlorine is widely employed in the pulp industry for oxidation of lignin during the pulp bleaching, however, its application is accompanied by concomitant formation of a number of toxic aromatic chlorine-containing products, 65,66 including dioxins. 67 The use of sodium hypochlorite for the pulp bleaching is accompanied by the formation of chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Observa-se a predominância de compostos de baixa massa molar (<1 kDa) em ambos os efluentes provenientes da planta de branqueamento. Nota-se também maior remoção de tais compostos, o que está de acordo com diversos autores que indicam que fração com massa molar <1 kDa é mais rapidamente degradada quando comparada à fração com massa molar >1 kDa (MARTIN, 1995;SONNENBERG;WIMER;ARD, 1995).…”
Section: Caracterização Do Efluente Após Degradaçãounclassified
“…Furthermore, some compounds, particularly those containing chlorine (measured by the parameter AOX) are recognizably recalcitrant because they contain chemical structures uncommon in nature, such as the carbon-chlorine bond [17], and their efficient removal depends on sufficient adaptation of the biological solids in the treatment system [15]. Various authors have also observed that high molecular mass (HMM) organic matter in bleaching effluents is more recalcitrant to biological treatment than low molecular mass (LMM) organic matter and that the proportion of HMM organic matter in the effluent may increase after biological treatment [18][19][20]. It has also been shown that the biodegradability of the HMM organic matter depends on the raw material and bleaching sequence used and can be improved by sufficient adaptation of the activated sludge to the particular effluent being treated [15].…”
Section: Introductionmentioning
confidence: 99%